The importance of product innovation in maintaining a competitive advantage - Ahmed Saeed Sarkar; Omer Mohammed Hazhar; Amjad Muhamed Rawa; Fayaq Othman Rezhwan (Mednarodno Inovativno Poslovanje)
Product innovation is crucial in creating and sustaining a competitive advantage for companies. Companies can differentiate themselves from competitors by constantly improving, introducing new products, and appealing to customers. The success of product innovation depends not only on how new the product is but also on its quality and Price. Therefore, the relationship between product innovation, Price, and quality is vital for creating and maintaining a competitive advantage. This study analyzes the relationship between product innovation and (price, quality) with a sustainable competitive advantage, the data shows that there is an effective and positive relationship between product innovation and price, quality. Additionally, we collected data through forum questionnaires and analyzed it using the multiple regression method, and We used SPSS version 25 for assistance in data analysis. So, the study can analyze the influence of the independent variables (product innovation) on the dependent variable (sustained competitive advantage). After analyzing the data, it was found that process innovation, product innovation, Price and quality positively impact sustained competitive advantage. The results also indicate that these three independent variables significantly affect the dependent variable.